Stimuli-responsive smart nanoparticles with well-defined random and triblock terpolymers for controlled release of an anticancer drug - OKTAY, BURCU; KAYAMAN APOHAN, NİLHAN; ÇUBUK, SONER (ELSEVIER, 2021)
Stimuli-responsive nanoplatforms have shown great potential especially in efficient drug release systems. The rate of the anticancer drug release, adverse side effects, and toxicity can be controlled by designing nanoplatforms. Herein, mesoporous hydroxyapatite (HAp) nanoparticles were prepared. Fluorescent and pH-responsive biocompatible well-defined polymer chains were covalently attached by one step and sequential surface-initiated ATRP. The diameter of HAp increased from 120 to 147 and 158 nm with copolymerization. Polyethyleneglycol, poly(dimethylamino)propyl methacrylamide), and poly(fluorescent methacrylate) chains enhanced stimuli responsiveness of drug delivery. The drug release of the DOX@HAp/terpolymer nanoparticles was low under physiological conditions (pH 7.4). However, the release rate of DOX increased when pH was decreased to 5.5. The results of cytotoxicity indicated that the DOX-loaded HAp/terpolymer nanoparticles exhibited high biocompatibility and also caused apoptosis of cancer cells.
Keywords: Porous HAp; Surface-initiated ATRP; Terpolymer; pH-responsive drug release